Analisa Pemanfaatan Energi Terbuang (Wasted Energy) pada Perencanaan Heater di PT Samudera Windu Cold Storage - Erlangga Atidhira Hadijaya; Fuazen; Joni Rahmadi (Syntax Literate, 2023)
One type of heat exchanger that is widely used is the shell and tube type heat exchanger. The feasibility of making this heat exchanger is seen from the use of heating fluid and heated fluid, how much economic value is obtained. From the data obtained, that in the process of making ice cubes using cold storage which is in the cooling process in the condenser using river water and has a high enough temperature, so that it can be used as a heating source. Through the concept of the Energy Management Program (PME) a heat exchanger with utilizing residual heat as a preheater for the use of water consumption for bathing, washing, and so on.